2016
DOI: 10.1509/jm.15.0229
|View full text |Cite
|
Sign up to set email alerts
|

Stock Returns on Customer Satisfaction Do Beat the Market: Gauging the Effect of a Marketing Intangible

Abstract: A debate about whether firms with superior customer satisfaction earn superior stock returns has been persistent in the literature. Using 15 years of audited returns, the authors find convincing empirical evidence that stock returns on customer satisfaction do beat the market. The recorded cumulative returns were 518% over the years studied (2000–2014), compared with a 31% increase for the S&P 500. Similar results using back-tested instead of real returns were found in the United Kingdom. The effect of cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
130
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(141 citation statements)
references
References 71 publications
6
130
0
5
Order By: Relevance
“…This is an important question since customer satisfaction, for example, has been shown to drive bottom-line performance of the firm (e.g., Fornell, Morgeson, and Hult 2016). But, in reality, it is not clear that firms' managers really know what their customers think of the firm's product/service offerings and why.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important question since customer satisfaction, for example, has been shown to drive bottom-line performance of the firm (e.g., Fornell, Morgeson, and Hult 2016). But, in reality, it is not clear that firms' managers really know what their customers think of the firm's product/service offerings and why.…”
mentioning
confidence: 99%
“…Additionally, a large and growing literature supports the significant firm performance benefits of successfully delivering such superior customer satisfaction (e.g., Akzoy et al 2008;Fornell, Mithas, Morgeson, and Krishnan 2006;Fornell, Morgeson, and Hult 2016). In their efforts to achieve these benefits, most large firms monitor the satisfaction of their customers with the firm's product/service offerings (e.g., Morgan, Anderson, and Mittal 2005) and use consumer survey (and other) data, combined with increasingly sophisticated analytical techniques to help uncover the drivers of customers' satisfaction and loyalty.…”
mentioning
confidence: 99%
“…Customer satisfaction is one of the most important intangible assets of a firm that affects its market value (Fornell et al 2016). Prior research suggests that high customer satisfaction leads to greater return on investment and cash flows (Aksoy et al 2008;Anderson et al 2004;Fornell et al 2006;Gruca and Rego 2005;Tuli and Bharadwaj 2009) as satisfied customers are more likely to be loyal, thereby protecting market share, lowering price elasticity as well as selling/marketing costs (Anderson et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…To the extent that the potential investors believe that customer satisfaction would have positive impacts on future cash flows of a firm, they will seek information about the customer satisfaction of the firms and use it to make their investment decisions. In fact, research has shown that customer satisfaction does matter to investors who take satisfaction information into account while making their investment decisions (Anderson and Mansi 2009;Fornell et al 2016;Luo et al 2014). While it is difficult and costly to reliably assess the customer satisfaction for a large number of firms on a regular basis, investors may rely on American Customer Satisfaction Index (ACSI), which is the leading measure of customer satisfaction in the U.S., to obtain information about relative customer satisfaction of the largest 300 companies in the U.S. consumer market (Fornell et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation